A Narrative Inquiry on the Challenges and Coping Mechanism of School Leaders in Higher Learning Institutions Amidst Pandemic - John Michael Aquino (Journal of Mathematics Instruction, Social Research and Opinion, 2023)
The current study seeks to discover the experiences of the school leaders towards their challenges during a pandemic and their coping mechanisms to provide quality education to the institution's students. The researcher applies narrative inquiry to a qualitative research design. A total of six deans and associate deans were selected as research participants through purposive sampling. Via an interview guide during the interview, the researcher gathered data and presented it using narratives. The results revealed that school leaders encountered many challenges, particularly in the immediate readiness of evaluation tools, accessibility of technology, relationships with coworkers, the University's learning continuity plan implementation, the execution of the course, and the systematic implementation of procedures. In contrast, the efforts made by the school leaders to battle the pandemic outbreak are vital for the education system to cope, including the delivery of webinars, training, and workshops, the availability of a plan for continuous learning, and the University's assistance to stakeholders. It is recommended that higher education institutions design and enhance their learning continuity plans, ensure that the manuals are appropriately disseminated, undertake curriculum enhancements for those programs requiring review, and follow the administration's instructions.